(raiz de 2+ raiz de 3)^2
Soluções para a tarefa
Respondido por
1
Olá!
A expressão:
![( \sqrt{2} + \sqrt{3} )^{2} ( \sqrt{2} + \sqrt{3} )^{2}](https://tex.z-dn.net/?f=%28+%5Csqrt%7B2%7D++%2B++%5Csqrt%7B3%7D+%29%5E%7B2%7D+)
Desenvolvemos o produto notável:
- Lembrando que √x . √x = √x² = x
![( \sqrt{2} + \sqrt{3} ) \times (\sqrt{2} + \sqrt{3} ) ( \sqrt{2} + \sqrt{3} ) \times (\sqrt{2} + \sqrt{3} )](https://tex.z-dn.net/?f=%28+%5Csqrt%7B2%7D++%2B++%5Csqrt%7B3%7D+%29+%5Ctimes++%28%5Csqrt%7B2%7D++%2B++%5Csqrt%7B3%7D+%29)
![2 + \sqrt{6} + \sqrt{6} + 3 2 + \sqrt{6} + \sqrt{6} + 3](https://tex.z-dn.net/?f=2+%2B++%5Csqrt%7B6%7D++%2B++%5Csqrt%7B6%7D++%2B+3)
![2 + 2 \sqrt{6} + 3 2 + 2 \sqrt{6} + 3](https://tex.z-dn.net/?f=2+%2B+2+%5Csqrt%7B6%7D++%2B+3)
![= 5 + 2\sqrt{6} = 5 + 2\sqrt{6}](https://tex.z-dn.net/?f=+%3D+5++%2B+2%5Csqrt%7B6%7D+)
A expressão:
Desenvolvemos o produto notável:
- Lembrando que √x . √x = √x² = x
Perguntas interessantes
História,
11 meses atrás
Inglês,
11 meses atrás
Matemática,
11 meses atrás
Pedagogia,
1 ano atrás
Física,
1 ano atrás